Systematic review on Cryptococcus neoformans/Cryptococcus gattii species complex infections with recommendations for practice in health and care settings - Mireille H. van der Torre; Rebecca A.J. Andrews; Emma L. Hooker; Annette Rankin; Susie Dodd (Clinical Infection in Practice, 2022)
Objectives: Cryptococcosis, a fungal disease that is mainly caused by Cryptococcus neoformans/Cryptococcus gattii species complex, can be life-threatening for immunocompromised individuals. Following notification of two inpatient cryptococcosis cases in Scotland, reported to ARHAI Scotland via the outbreak and incident reporting system, an investigation was prompted towards the cause and sources of the infectious agent. Limited evidence is available on cryptococcosis in Scotland and therefore a systematic literature review on nosocomial C. neoformans/C. gattii species complex infections was performed. Methods: A targeted literature review was produced using a defined methodology as described in the National Infection Prevention and Control Manual: Development Process (https://hpspubsrepo.blob.core.windows.net/hps-website/nss/2892/documents/1_combined-nipcm-methodology-v3.1.pdf). Three literature databases (MEDLINE, EMBASE and CINAHL) were searched, evidence was screened for relevance, relevant studies were critically appraised and summarised to form evidence-based conclusions and recommendations for practice in health and care settings. Results: Out of the 3489 search results, 71 papers were included to form recommendations in this review. Within the evidence base, the majority of papers were found to be of low to moderate quality (SIGN50 level 3 or level 4). The evidence suggests that immunocompromised patients are most at risk of a C. neoformans/C. gattii species complex colonisation/infection which can involve the lungs, meninges and/or brain, and other sites (e.g. skin and/or soft tissue, bone, eye, and lymph nodes). Due to its ability to undergo genotypic and phenotypic changes, Cryptococcus spp. can stay dormant in its host and therefore incubation periods can vary between 6 weeks and 2 years. C. neoformans is primarily found in bird droppings whereas C. gattii is mainly associated with trees and the two transmission routes for Cryptococcus spp. are airborne and donor-derived. Conclusions: Although acquisition in the UK cannot be determined from these studies, conclusions and category B recommendations have been made for practice in health and care settings on the basis of the relevant studies found in literature.